The Effectiveness of an Interactive Multimedia Psychoeducational Approach to Improve Financial Competence in At-Risk Youth: A Pilot Study - Bradley Klontz; Caesar Pacifici; Lee White; Carol Nelson (Journal of Financial Therapy, 2011)
In recent years, a growing number of initiatives have been aimed at increasing financial literacy among youth in America. However, these efforts have tended to target mainstream populations, and failing to adequately address the backgrounds, learning, and psychological needs of at-risk youth. This study piloted a curriculum on money management that presented a basic set of financial skills via story situations and characters that are meaningful to at-risk youth using a dynamic interactive multimedia online delivery to heighten youths’ interest to learn. The approach also helped at-risk youth gain insight into their money beliefs and psychological barriers to success, integrating change theory and techniques designed to enhance their motivation to change. Eighty-eight Job Corps participants were randomly assigned to treatment and control conditions. Results showed that the interactive multimedia curriculum produced significant gains in youth’s financial knowledge and confidence in money management skills.
Keywords: financial therapy; marriage and family therapy; social work; psychology